Hukum dan Etika Profesi Pengusaha di Bidang Perikanan - Lestari, Nurdiana; Moonti, Roy Marthen; Ahmad, Ibrahim (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Indonesia, as the largest archipelagic country in the world, has enormous fisheries potential with a sea area of 5.8 million km². The fisheries sector contributes significantly to the national economy, but faces serious challenges in the form of illegal fishing practices, the use of environmentally damaging fishing gear, and weak law enforcement. This research aims to analyze the role of law and professional ethics in supporting the sustainability of the fisheries sector. A normative approach is used by examining primary, secondary, and tertiary legal materials. The results showed that Law No. 45/2009 on Fisheries has provided a strong legal basis, but its implementation is constrained by weak coordination between institutions and limited monitoring infrastructure. On the other hand, the application of professional ethics by entrepreneurs is still not optimal, with many cases of using illegal fishing gear and injustice to small fishermen.